A study of male participation in early childhood education. Issue 5 (2014) - Dora Ho; Haze Lam
<x xml:space="preserve"> Abstract </x> Purpose – The function of early childhood education (ECE) has shifted from mothering to nurturing child development in Hong Kong. Teaching in kindergartens seems to be more attractive to men nowadays. The purpose of this paper is to explore the issues of male participation in ECE through a case study of a local kindergarten. Design/methodology/approach – A case study methodology was used in the research design and the data were collected through semi‐structured interviews. The interviewees all came from a single, case study school, and included the kindergarten principal, head teacher, teachers, both Chinese and foreign nationals, and parents. Findings – The findings of the study indicated that most of the school staff support hiring male teachers in kindergartens and perceive that male teachers play an important role in educating young children. On the other hand, the views of parents who participated in the study were divided. This reflects gender bias on the part of parents. Originality/value – Minimal research on male participation in kindergartens has been conducted in Hong Kong. The findings of the study shed some light on the issues of male participation in ECE in a Chinese context. It is argued that overcoming the low participation of male teachers in ECE will require changes in deeply rooted institutional and management practices. From a wider perspective, providing better career prospects and improving the professional status of kindergarten teachers will attract more men to teach in kindergartens. <ack> <x xml:space="preserve"> Acknowledgements </x> The authors wish to express their gratitude to Professor Mok Ka Ho Joshua, who offered helpful comments on the earlier version of this paper. </ack>